Correction to: Determinant roles of dendritic cell-expressed Notch Delta-like and Jagged ligands on anti-tumor T-cell immunity. Issue 1 (7th May 2019) - Tchekneva, Elena E.; Goruganthu, Mounika U. L.; Uzhachenko, Roman V.; Thomas, Portia L.; Antonucci, Anneliese; Chekneva, Irina; Koenig, Michael; Piao, Longzhu; Akhter, Anwari; de Aquino, Maria Teresa P.; Ranganathan, Parvathi; Long, Nicholas; et al.
Abstract : Following publication of the original article [1], the author reported the wrong version of Figs. 5 and 7 have been published. The correct version of the figures can be found below: